Land property in the Decree of the Polish Committee of National Liberation of 6 September 1944 on the implementation of the land reform – selected issues - Kremer, Elżbieta (Przegląd Prawa Rolnego, 2024)
The subject of consideration is the notion of land property contained in the Decree of the Polish Committee of National Liberation on the implementation of a land reform. Although the term was used in the Decree there was no definition of it in the Decree. And yet, a proper establishment of its meaning is important for determining the scope of the Decree, especially because despite the passage of years, the concept of landed property is still the subject of administrative and judicial-administrative proceedings. Difficulties concern mainly the question whether there actually exists a connection between a landed property and agricultural activities, either directly or through a functional relationship.